Impact absorption capacity of 3D-printed components fabricated by fused deposition modelling. (15th July 2016) - Tsouknidas, A.; Pantazopoulos, M.; Katsoulis, I.; Fasnakis, D.; Maropoulos, S.; Michailidis, N.
Abstract: Despite additive manufacturing emerging as an effective alternative to conventional manufacturing methods, ought partially to the support of open source communities, little is known about the shock absorbing properties of the parts produced. An open source fused deposition modelling device was employed to fabricate 3D polymeric structures and their shock mitigating properties were evaluated. The effect of commercially available layer heights, infill patterns and density on the energy dissipation properties of the printed PLA (polylactic acid) cylinders was examined. A strong dependency of the apparent density on the impact absorption capacity, both in terms of sock mitigation and energy dissipation, of the components was determined whereas the effect of layer height was less pronounced and that of the filling pattern negligible. Results showed that porous specimens were prone to process parameter changes, an effect, gradually fading towards higher densities. Graphical abstract: Highlights: 3D printed polymeric components as cost effective shock mitigation structures. Effect of commercially available printing configurations on the energy dissipation properties of the fabricated specimen. Infill density had the strongest influence on energy absorption, followed by layer height and infill pattern respectively. Less dense specimens were more prone to process parameter changes, an effect that faded towards higher densities.